Juridical Analysis of Evidence in Criminal Offenses Involving Information Technology in Decision Number 554/PID.B/2025/PN Jmr - Aisyah Mulya Alfiyanti (Media Hukum Indonesia (MHI), 2026)
Advances in information and communication technology have changed many parts of life, including how people commit crimes and how they do it. Digital crimes use new technologies, such as online fraud, hacking, and sharing illegal content. This is a change from the way crimes were done before.2 This situation presents novel challenges for the criminal justice system, especially concerning evidence. Electronic evidence has become very important as a modern type of proof. Nonetheless, enquiries regarding its validity, authenticity, and integrity persist in the legal context. This article aims to analyse the legal rationale articulated by the judge in Decision No. 554/Pid.B/2025/PN Jmr, specifically concerning the admissibility of electronic evidence. It will also look at whether electronic evidence meets the standards set by criminal procedure law and the Electronic Information and Transactions (ITE) Law. This normative juridical research employs a case study methodology, focusing on the examination of judicial rulings and pertinent regulations. The results show that the judge looked at electronic evidence in a way that followed the ITE Law. Electronic evidence can be considered valid if it meets the formal and material requirements. Judges' decisions show that people are working to change evidence law and technology to make digital criminal cases more certain. However, there are a few things that need to be improved, such as ways to check the authenticity and integrity of electronic data and ways to collect and handle digital evidence.